ARTIFICIAL INTELLIGENCE AS A TOOL FOR DEVELOPING COMMUNICATIVE COMPETENCE IN FOREIGN LANGUAGE LEARNERS - Tolkyn Dildabek; Nabidullin S. Aibolat (Research Retrieval and Academic Letters, 2025)
This paper examines the effectiveness of artificial intelligence technologies in developing communicative competence among foreign language learners. The study provides an overview of major theoretical perspectives on communicative competence, highlighting its linguistic, sociolinguistic, discourse, and strategic components. The literature review demonstrates that AI supports personalized learning, creates interactive language environments, and offers rapid, accurate feedback. In the empirical part, ChatGPT, ELSA [6] Speak, Duolingo [4], and Grammarly [5] were used, and improvements in speaking, listening, reading, and writing were analyzed using a mixed-methods approach. The results indicate significant skill enhancement, reduced speaking anxiety, increased motivation, and greater learner autonomy. Overall, the study confirms that AI is an effective and accessible tool for enhancing communicative competence.